Nutritional management for failure to thrive in patient with underlying osteogenesis imperfecta - Ing, C.L.T.; Ying, C.Y.; Amira Nadiah, A.B. (2021)
Assessment A 5-year-11-month-old Malay girl with Osteogenesis Imperfecta (01) type I, presented with recurrent fractures, blue sclera, and deformed teeth, was referred for personalised individual nutrition counselling as part of a multidisciplinary treatment plan. Staying with her family, she is cared for full-time by her mother. Being the 4th child among 5 siblings, she has no family history of chronic diseases or bony deformities. Born following a full-term pregnancy by spontaneous vaginal delivery with a normal birth weight (3.6kg), the patient experienced failure to thrive (FTT). During the consultation, height (102cm) and weight (14.9kg) showed a slight improvement but were still under the 3rd percentile based on the WHO growth chart. No latest biochemical and clinical data were available. The dietary assessment shows compliances towards previous recommendations with an estimated intake of energy (1663kca1/day), protein (50g/day), and calcium (1053mg/day) all meeting at least 80% of requirements. Diagnosis Her diagnoses include increased nutrient needs (energy and protein) (NI-5.1) related to increased demand due to FTT and 01 as evidence by energy and protein requirement of 100kcal/kg and 3.0g/kg respectively and growth rate below expectation (NC-3.5) related to the physical impetus for increased nutrient needs (FTT and 01) and decreased ability to consume sufficient energy due to deformed teeth as evidence by length and weight-for-age below 3rd percentile of WHO growth chart. Intervention The patient was re-emphasized on high caloric, high protein diet with adequate calcium and Vitamin D intake to achieve adequate energy protein intake while promoting healthy height and weight gain. Monitoring & Evaluation A follow-up 2 weeks post-consultation shows improvement where all requirements were met (100%). She was encouraged to continue with high caloric, protein, and calcium meals. Lifelong good nutrition is important for a patient with a genetic disorder to grow and develop normally while preventing health complications and improving life qualities.